The diagnostic performance of radiomics-based MRI in predicting microvascular invasion in hepatocellular carcinoma: A meta-analysis - Liang, Gao; Yu, Wei; Liu, Shuqin; Zhang, Mingxing; Xie, Mingguo; Liu, Min; Liu, Wenbin (Frontiers in Oncology, 2023)
Abstract Objective The aim of this study was to assess the diagnostic performance of radiomics based-MRI in predicting microvascular invasion (MVI) in hepatocellular carcinoma (HCC). Method The databases of PubMed, Cochrane library, EMBASE, Web of Science, OVID Medline, Springer and Science Direct were searched for original studies from their inception to 20 August 2022. The quality of each study included were assessed according to QUADAS-2. The pooled sensitivity, specificity, positive likelihood ratio(PLR), negative likelihoood ratio(NLR) and diagnostic odds ratio(DOR) were calculated. The summary receiver operating characteristic (SROC) curve was plotted and the area under the curve (AUC) was calculated to evaluate the diagnostic accuracy. Spearman’s correlation coefficient and subgroup analysis were performed to explore the source of the heterogeneity. Deek’s test was used to assess publication bias. Results 15 studies involving 981 patients were included. The pooled sensitivity, specificity, PLR, NLR, DOR and AUC were 0.79(95%CI: 0.72~0.85), 0.81(95%CI: 0.73~0.87), 4.1(95%CI：2.9~5.9), 0.26(95%CI: 0.19~0.35), 16(95%CI: 9~28) and 0.87(95% CI: 0.84~0.89), respectively. The results showed great heterogeneity among the included studies. The results of subgroup analysis showed that hepatocyte-specific contrast media(HSCM) had equivalent sensitivity and equivalent specificity compared to the other set. LASSO method had high sensitivity and specificity than other method, respectively. Investigated area of region of interest(ROI) had high specificity compared to volume of interest(VOI). Deek’s test indicate there was no publication bias(P=0.71). Conclusion Radiomics based-MRI has high accuracy in predicting MVI in HCC, and it can be considered as a noninvasive method for assessing MVI in HCC.